2019
DOI: 10.1016/j.joen.2018.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Root Canal Shaping Using Nickel Titanium, M-Wire, and Gold Wire: A Micro–computed Tomographic Comparative Study of One Shape, ProTaper Next, and WaveOne Gold Instruments in Maxillary First Molars

Abstract: Highlights • This study compared canal shaping with the rotary One Shape (nickel titanium), rotary ProTaper NEXT (M-Wire), and reciprocating Primary WaveOne Gold (Gold wire) after glide path preparation with K-Files, One G, and ProGlider. • No statistically significant difference in the mean centering ratios at the apical, midroot, and coronal levels of the various glide path groups in combination with the shaping instruments. • WaveOne Gold exhibited the lowest transportation values at all levels with ProGlid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 28 publications
5
34
0
5
Order By: Relevance
“…ese results could be explained by the improved flexibility of WOG that would reduce canal transportation and maintain the canal geometry. e shaped canals demonstrated some degrees of canal transportation which is consistent with previous studies [11,[13][14][15]. e slight canal transportation in XPS and WOG toward the outer side at the canal exit level might be attributed to the tendency of the NiTi file to return to its original shape by the restraining forces of the file [3].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…ese results could be explained by the improved flexibility of WOG that would reduce canal transportation and maintain the canal geometry. e shaped canals demonstrated some degrees of canal transportation which is consistent with previous studies [11,[13][14][15]. e slight canal transportation in XPS and WOG toward the outer side at the canal exit level might be attributed to the tendency of the NiTi file to return to its original shape by the restraining forces of the file [3].…”
Section: Discussionsupporting
confidence: 89%
“…e WOG with the apical size of 0.25 mm and variable taper design of 7% maintained the canal exit in the original place with slight transportation. Previous studies revealed the ability of WOG to better perform canal shaping when compared with WaveOne [11], ProTaper Gold [14], Pro-Taper Next [15], and One Shape [15], respectively. Also, Ozyürek et al [12] found that the WOG caused a lower level of resin removal in simulated canals with double curvature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Although previous study reported the superiority of WaveOne Gold over RECIPROC Blue in canal centering and transportation, 26 another study showed that no difference was found in canal transportation between HyFlex EDM and WaveOne Gold; these discrepancies in the results may be attributed to the study design where they used simulated resin canals which is not the case in this study where natural canals were used and analyzed with the highly accurate micro-CT. 31 It has been reported that WaveOne Gold showed a better centering ability than One Shape which is evident in this study. 32 Previous studies showed similar performance for WaveOne Gold. 25,33,34 It was found that all the four groups showed a centering ratio more than one at the apical level indicating the tendency of all the instruments used to prepare more of the outer surface of the canal curvature rather than the inner surface.…”
Section: Discussionmentioning
confidence: 88%
“…Having removed the fractured instrument, a size 30 K-File was fitted loose in the root canal up to working length as confirmed radiographically and with an electronic apex locator (ProPex, Dentsply, Sirona). According to the file selection criteria outlined by Van der Vyver et al (2019) 38 for WaveOne Gold files, a size large WaveOne Gold File (45/05) was selected for canal preparation.…”
Section: Several Authors Have Highlighted Additional Causesmentioning
confidence: 99%